A Clinical Study on Efficacy of Ajeya Ghrita in Dushivisha Janya Lakshana (AYUSHDHARA, 2021)
In modern era or day to day life cumulative toxicity (Dushivisha) increases the need for antioxidants as the body attempts to neutralize the harmful substances. The factors such as Viruddhahara and Ahitahara, fast foods and cold beverages, alcohol, tobacco, pesticides, metals and pollutants etc. can be considered under Dushivisha (cumulative poison). Aggravate Dosha vitiate the Dhatu (elements of body) specially Rakta Dhatu, it deposits in body tissues due to mild potency in nature, it covered by Kapha dosha and produces many diseases in favorable condition. Acharya Sushruta in Kalp sthana mentioned Ajeya Ghrita as a best remedy for the management of Dushivisha derived diseases. The content of Ajeya ghrita have Laghu, Rukhsha, Tiksna, Katu, Ushna, Kushthaghna, Krimighana Vishghna and antioxidant properties can help the breakdown the pathogenesis of Dushi visha. This formulation is given in 30 patients which is divided in two group having 15 patients in each group in oral dose of 12gm BD with lukewarm water for 30 days with follow up 30 days. Patient having sign and symptoms of fever, Kotha (skin allergies), Kasa (cough), Trishna (increased thirst), abdominal pain, recurrent Avipaka (indigestion)/ Arochak (anorexia), recurrent Chardi (vomiting)/ nausea, recurrent Shirahshool (headache)/ dizziness, recurrent Jwara (fever), recurrent Atisara (diarrhea), premature aging (wrinkling of skin, greying and loss of hair etc.), Smritinasha (loss of memory), recurrent Daurbalya (weakness), result found 1 patient (6.67%) were completely remitted in Group A while group B not found. 4 patients (26.66%) Group A, while in Group B, 3 (20%) were moderately improved respectively. 5 patients (33.33%) were no relief in group A and 4 (40%) in group B, no relief in any symptoms.